Analysis of wastewater treatment technologies: A bibliographic review - Jiménez Tamayo, Fabiola Maribel (2023)
Effective management of effluents generated by the activity is essential to protect public health and conserve the environment, especially when 2,4 billion people still lack access to essential health services. Pollution of water resources in Latin America threatens biodiversity and health, making efficient and sustainable wastewater treatment essential to meet the growing demand for drinking water and comply with stricter environmental regulations. The objective was to identify the main technologies developed for wastewater treatment. The literature review was carried out using the PRISMA methodology, which consists of four stages: identification, selection, eligibility and inclusion. Physical, mechanical, biological, chemical and advanced methods for wastewater treatment were identified. The effectiveness of biological methods, such as activated sludge and constructed wetlands, is emphasized to eliminate organic matter, reaching efficiencies greater than 80% in domestic waters and up to 88% in industrial effluents. The usefulness of physical-chemical processes in the elimination of specific compounds was also highlighted. It is concluded that the combination of technologies in hybrid systems is essential for a comprehensive treatment and the emergence of membranes, such as nanofiltration and ultrafiltration, for the selective elimination of contaminants is noted. Furthermore, the trend towards the use of sustainable processes is highlighted, which includes the use of waste as treatment materials, the generation of useful by-products and the reduction of energy consumption.